Update on mutations in glucokinase (GCK), which cause maturity-onset diabetes of the young, permanent neonatal diabetes, and hyperinsulinemic hypoglycemia. - Osbak, K; Colclough, K; Saint-Martin, C; Beer, N; Bellanné-Chantelot, C; Ellard, S; Gloyn, A (2009)
Glucokinase is a key regulatory enzyme in the pancreatic beta-cell. It plays a crucial role in the regulation of insulin secretion and has been termed the glucose sensor in pancreatic beta-cells. Given its central role in the regulation of insulin release it is understandable that mutations in the gene encoding glucokinase (GCK) can cause both hyper- and hypoglycemia. Heterozygous inactivating mutations in GCK cause maturity-onset diabetes of the young (MODY) subtype glucokinase (GCK), characterized by mild fasting hyperglycemia, which is present at birth but often only detected later in life during screening for other purposes. Homozygous inactivating GCK mutations result in a more severe phenotype presenting at birth as permanent neonatal diabetes mellitus (PNDM). A growing number of heterozygous activating GCK mutations that cause hypoglycemia have also been reported. A total of 620 mutations in the GCK gene have been described in a total of 1,441 families. There are no common mutations, and the mutations are distributed throughout the gene. The majority of activating mutations cluster in a discrete region of the protein termed the allosteric activator site. The identification of a GCK mutation in patients with both hyper- and hypoglycemia has implications for the clinical course and clinical management of their disorder.